Downward remagnetization of a ∼74-m-thick zone in lake sediments from palaeo-Lake Idaho (NW United States): locating the Gauss/Matuyama geomagnetic boundary within a dual-polarity zone - Allstädt, Frederik J.; Appel, Erwin; Rösler, Wolfgang; Prokopenko, Alexander A.; Neumann, Udo; Wenzel, Thomas; Pross, Jörg (Geophysical journal international, 2020)
SUMMARY. Remagnetization is an important issue in palaeomagnetism. Here, we discuss an extraordinarily thick (∼74 m) dual-polarity transition zone between the Gauss and Matuyama Chrons. The studied succession is from a drill core through lacustrine sediments of palaeo-Lake Idaho (Snake River Plain, NW United States of America) that are intercalated with basalt units. We identified detrital Ti-rich titanomagnetite and magnetite in lamellar exsolutions as the main carriers of a primary remanence, likely derived from the basalts that erupted in the Snake River Plain. Stepwise thermal demagnetization revealed a single-component remanent magnetization with reversed and normal polarities above and below the transition zone, respectively. Based on rock-magnetic results, microscopic observations, and previously known events in the evolution of palaeo-Lake Idaho, the reversed-polarity component in the transition zone represents a secondary chemical remanent magnetization caused by magnetic mineral alteration or partial neo-formation of magnetite, in association with strong depletion of the primary detrital magnetic minerals that affected a wide depth range below the level where the remagnetization event occurred. This remagnetization event was most likely related to lake-level lowering and partial desiccation of palaeo-Lake Idaho. Understanding the nature and origin of the remagnetization allows to identify the polarity boundary in the unusual case of a secondary magnetization with reversed polarity produced downward in a sequence to an extraordinary large depth. Based on available age information, the observed reversal represents the Gauss/Matuyama boundary, which provides an important age constraint for palaeoclimatic interpretation of the succession
Gesehen am 26.10.2020